Sacred and “Archetypal Images”. Religion and New Forms of Spirituality in Postmodern Society - Camorrino, Antonio (Italian Sociological Review, 2026)
The hypothesis underlying this article is that the social relationship with the sacred in postmodern Western society revolves around (at least) two juxtaposed polarities of the imagery: the Christian religion (especially Catholic), on the one hand, pertains to a “diurnal order” in which the transcendence of God – however weakened – still guarantees and imposes a division between the worldly and the otherworldly; the relationship with the sacred of new forms of spirituality, on the other hand, originates and ends on the immanent level, hence a certain degree of “undifferentiation” that refers to a “nocturnal order” (Durand, 1999). These polarities of the imagery are shaped by different “myths”. The first – the one underlying Christianity – is characterized by a predominant “aerial” symbolism, while the second by an “aquatic” one (new forms of spirituality). However, in postmodern society, we witness a process of symbolic disarticulation, because the “‘archetypal images’” (Jacobi, 2004, p. 61) reveal themselves as ‘blurred’ to the consciousness. Likewise, this phenomenon produced a hiatus between meanings and experience: hence, dialectically, the meanings given to experience are also ‘blurred’. This is due to the collapse of “ambivalence”, which is instead the main feature of the “archetypal images” released by all the elements (Bachelard, 2005). It follows that it is very hard for individuals socialized within these peculiar imageries to live a “full” experience of the sacred: this domain has traditionally ‘contained’ the “dramas” of existence, by revealing its “universal” meaning to the “total consciousness of human being” (Eliade, 2009b, p. 134). Today, it no longer seems to be the case. This paper aims to scrutinize the above-mentioned social changes through the analytical perspective of depth sociology and sociology of imagery.